On the sufficient conditions of the localization of the Fourier-Laplace series of distributions from liouville classes - Ahmedov, Anvarjon A.; Rasedee, Ahmad Fadly Nurullah; Rakhimov, Abdumalik (IOP Publishing, 2013)
In this work we investigate the localization principle of the Fourier-Laplace series of the distribution. Here we prove the sufficient conditions of the localization of the Riesz means of the spectral expansions of the Laplace-Beltrami operator on the unit sphere.